Movement ecology of the white seabream Diplodus sargus across its life cycle: a review - Giacalone, Vincenzo Maximiliano (2022)
The white seabream Diplodus sargus (L., 1758) (Osteichthyes, Sparidae) is a littoral species living mainly in rocky habitats and distributed in the eastern Atlantic and the Mediterranean. This species is targeted by artisanal and recreational fisheries and presents a high commercial importance. Although classified by IUCN as a "least concern" species, it has been the object of marine ranching and restocking initiatives to counteract locally intense exploitation. Here, we review the current knowledge on the movement ecology of white seabream given the relevance of animal movement in ecological and behavioral studies and their potential application in management and conservation. The literature on this topic was analyzed in order to summarize the results of past research and to identify the gaps that still exist on the matter. We reviewed a total of 27 papers focusing on the movement ecology of white seabream, where acoustic telemetry (n = 12), underwater visual observation and traditional tagging (n = 6), genetic analysis (n = 6), and otolith microchemistry (n = 3) were used. While the first three methods were applied to juvenile and adult fish, the last one was also used with larvae, which have been the object of experimental trials to ascertain their swimming abilities. The largest amount of information on activity rhythms (diurnal with a few exceptions), movement patterns (short distances), homing (ability to come back to the capture site), site fidelity (high), and home range (< 200 ha on average and highly related with seabed morphology) were obtained through acoustic telemetry, whose main limitation is the minimum body size required for its application. The environmental variables found to affect movement patterns in this species are water temperature (which triggers spawning-based vertical movements), local sea conditions (which affect short-scale movements in juveniles), and the main seabed features (orientation and habitat type). The main gaps identified, which need more extensive research and some technological improvements, include the study of the effects of environmental variables on fish movements and further investigations on the movement patterns of juveniles.